Hydrocarbons in the upper troposphere and lower stratosphere observed from ACE‐FTS and comparisons with WACCM. Issue 4 (20th February 2013) - Park, Mijeong; Randel, William J.; Kinnison, Douglas E.; Emmons, Louisa K.; Bernath, Peter F.; Walker, Kaley A.; Boone, Chris D.; Livesey, Nathaniel J.
Abstract : [1] Satellite measurements from the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE‐FTS) are used to examine the global, seasonal variations of several hydrocarbons, including carbon monoxide (CO), ethane (C2 H6 ), acetylene (C2 H2 ), and hydrogen cyanide (HCN). We focus on quantifying large‐scale seasonal behavior from the middle troposphere to the stratosphere, particularly in the tropics, and furthermore make detailed comparisons with the Whole Atmosphere Community Climate Model (WACCM) chemistry climate model (incorporating tropospheric photochemistry, time‐varying hydrocarbon emissions, and meteorological fields nudged from reanalysis). Comparisons with Microwave Limb Sounder (MLS) measurements of CO are also included to understand sampling limitations of the ACE‐FTS data and biases among observational data sets. Results show similar overall variability for CO, C2 H6, and C2 H2, with a semiannual cycle in the tropical upper troposphere related to seasonallyvarying sources and deep tropical convection, plus a maximum during Northern Hemisphere summer tied to the Asian monsoon anticyclone. These species also reveal a strong annual cycle above the tropical tropopause, tied to annual variations in the upward branch of Brewer‐Dobson circulation. HCN reveals substantial differences from the other species, due to a longer photochemical lifetime and a chemical sink associated with ocean surface contact, which produces a minimum in the tropical upper troposphere not observed in the other species. For HCN, transport to the stratosphere occurs primarily through the Asian summer monsoon anticyclone. Overall, the WACCM simulation is able to reproduce most of the large‐scale features observed in the ACE‐FTS data, suggesting a reasonable simulation of sources and large‐scale transport. The model is too low in the Southern Hemisphere subtropics during Austral spring, which indicates underestimate of biomass burning emissions and/or insufficient vertical transport in the model. Key Points: Climatology of hydrocarbons in the UTLS Comparison of ACE‐FTS measurements to the WACCM4 simulations Variability of CO, C2 H6, C2 H2, and HCN in the UTLS